2021
DOI: 10.1155/2021/4850020
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Signal Recognition Based on APSO‐RBF Neural Network to Assist Athlete’s Competitive Ability Evaluation

Abstract: The advanced analysis and research methods of big data will provide theoretical support for the integration of athletes’ talent training. The advanced technological methods of big data will also give full play to the advantages of tapping the potential of talents and actively improve the success rate of grassroots young athletes. This paper proposes an improved Adaptive Particle Swarm Optimization (APSO) algorithm for the optimization of radial basis function (RBF) neural network parameters. The basic structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The hidden layer node produces a large output when the input signal is close to the basis function's central range. According to the RBF neural network model, the RBF neural network's training algorithm is investigated, and the K-means clustering algorithm is used to determine the hidden layer node center, hidden layer node width, and output weight of the network, as well as the network model framework [ 4 ]. The impact of the number of hidden layer nodes and distribution coefficient on the accuracy of the RBF neural network model is investigated using an empirical formula and a comparative test method, and the two parameters are finally determined to complete the RBF neural network model's establishment.…”
Section: Introductionmentioning
confidence: 99%
“…The hidden layer node produces a large output when the input signal is close to the basis function's central range. According to the RBF neural network model, the RBF neural network's training algorithm is investigated, and the K-means clustering algorithm is used to determine the hidden layer node center, hidden layer node width, and output weight of the network, as well as the network model framework [ 4 ]. The impact of the number of hidden layer nodes and distribution coefficient on the accuracy of the RBF neural network model is investigated using an empirical formula and a comparative test method, and the two parameters are finally determined to complete the RBF neural network model's establishment.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%